European Cancer Summit 2022 submission for Survivoship and Quality of Life NetworkEffect of Pain Neuroscience Education after breast cancer surgery on pain, physical and psychosocial functioning: a double-blinded randomized controlled trial (EduCan trial). (March 2023) - Dams, Lore; Van der Gucht, Elien; Haenen, Vincent; Devoogdt, Nele; Smeets, Ann; Morlion, Bart; Bernar, Koen; Godderis, Lode; De Vrieze, Tessa; Moloney, Niamh; Van Wilgen, Paul; Fieuws, Steffen; et al.
Abstract: Background: Approximately one in five women experiences persistent pain after breast cancer surgery. Despite the effectiveness of different physical therapy modalities (e.g., manual therapy, physical activity), pain and associated limitations in daily functioning remain common. Recently, there has been a greater awareness of the role of education in the treatment of pain. The goal of educational interventions is to help patients better understand, manage and cope with their pain. Currently, these are often limited to instruction based on a more biomedical approach to pain and the administration of pain medications. Increased understanding of the neurophysiology of pain resulted in a different educational approach. Pain neuroscience education (PNE) aims to reconceptualize pain away from the biomedical model towards a biopsychosocial understanding, in order to decrease the threat value of pain. This double-blinded randomized controlled trial investigated whether PNE, in addition to best-evidence physiotherapy after breast cancer surgery, was more beneficial than biomedical education on pain-related, physical and psychosocial functioning. Methods: Three educational sessions were given in addition to a four-month physiotherapy program starting immediately postoperative. The content of the educational interventions differed between the intervention (PNE, n=92) and control group (biomedical pain education, n=92). Additional educational and physiotherapy sessions were provided at six, eight and twelve months postoperatively. The primary outcome was the change in pain-related disability (Pain Disability Index) after twelve months. Secondary outcomes were pain intensity, upper limb function, physical activity and psychosocial functioning. All outcomes were evaluated pre-and postoperatively, and at four, six, eight, twelve and eighteen months. Results: Change in pain-related disability from baseline to twelve months postoperatively did not differ between groups (p=0.525). Secondary outcomes yielded similar results. Conclusions: Adding six sessions of PNE to physiotherapy immediately after breast cancer surgery did not result in a better course of functioning up to eighteen months postoperatively as compared to biomedical pain education. This finding broadens our understanding of PNE in this population and provides the basis for future research to fine-tune the optimal delivery format. Instead of imposing a one-size-fits-all formula, future research should investigate the effectiveness of a more patient-tailored PNE approach, based on a patient's specific needs and readiness.